TO STUDY THE EFFICACY OF KANCHNAR GUGGULU AND DASHMOOL MATRA BASTI IN THE MANAGEMENT OF VATASHTHEELA W.S.R TO BENIGN PROSTATIC HYPERPLASIA - Gupta Arjun; Gupta Pooja; Sharma Rini (International Journal of Ayurveda and Pharma Research, 2019)
Benign prostatic hyperplasia is a common senile disease. It is a non-cancerous [benign] enlargement of the prostate gland, also called as fibromyoadenoma. It is involuntary hyperplasia due to disturbance of the ratio and quantity of circulating androgens and estrogens. As the age advances the serum testosterone levels slowly but significantly decreases, but levels of oestrogenic steroids are not decreased equally. According to this theory the prostate enlarges because of increased oestrogenic effects. It is likely that the secretion of intermediate peptide growth factors plays a part in the development of BPH. Vatashtheela as described in Ayurveda, closely resembles benign prostatic hyperplasia of modern medicine in its signs and symptoms. In the Vatashtheela, Mutravaha Srotodushti and vitiation of Vata and Kapha Doshas are involved. So Vata Kapha pacifying drugs along with Matra Basti considered to be helpful in reducing the size of prostate and enhancing the tonicity of urinary bladder.This study was conducted to find out the potency of Ayurvedic regimen of Kanchnar Gugglu orally and Dashmool Tail Matra Basti for the treatment of Vatashtheela as the Kanchnar Gugglu is having Granthihar property and Dashmool Tail pacifies Vata and having Tridoshghana, Deepana, Anulomana, Shothghana and Shoolghana properties.The drug Kanchnar Gugglu was given to 30 patients of group -1, with the dose of 500mg TDS before meals for 30 days. And Dashmool Tail Matra Basti was given to 30 patients of group – 2, with the dose of 50ml once a day for 15 days.